The young skater - Smith, A. D. (Clinics in Sports Medicine, 2000)
Figure skating is one of the best lifetime sports. Participants may skate alone or with a group, recreationally or competitively, at all ages and at all skill levels. As a sport that improves physical fitness, skating builds strength, flexibility, and cardiopulmonary endurance. As a weight-bearing or high-impact activity, it is one of the best sports for increasing bone mineral density and perhaps for preventing osteoporosis. At least half of all competitive figure skating injuries appear preventable. Boots should be as flexible as the skater can control and should be carefully fitted. Normal flexibility of lower extremity muscles, especially in the growing athlete, markedly decreases the incidence of overuse symptoms of the knee. Core body strength is critical for controlling high-impact jump landings and decreasing injuries to the spine, pelvis, and hip girdle. Adequate shoulder strength is required for pair skaters and ice dancers. A well-designed off-ice training program decreases injury incidence and enhances performance. Assisting these dedicated athletes is truly rewarding as they train and compete at their highest potential, with passion for their sport.